RUSSIAN IDENTITY AND SPECIFICITY OF INTER-ETHNIC COMMUNICATION OF DAGESTAN PEOPLES - Sahbanova, M M (History, Archeology and Ethnography of the Caucasus, 2016)
Basing on the results of sociological research the author of the article shows the expressiveness of positive Russian identity of the Dagestan people and its reflection on the nature andfrequency of interethnic communication. It has been established that the surveyed Dagestan people are about to maintain interethnic contacts in almost all spheres of social interaction, and there are not negative attitude to the representatives of other ethnic communities, in their setings but they are negatively disposed to the migration of representatives of other ethnic groups to their territory.
Keywords: Russian identity; Dagestan peoples; interethnic communication; ethnic behavior